Complicated Infective Endocarditis Limited to a Chiari Network - Olufolahan Carrena; Oluchukwu Oluoha; Amr Wahba; Derek Eshun; Maria Endsley; Henry Okafor (Case Reports in Cardiology)
Introduction. The Chiari network is an uncommon vestigial structure of the heart that is often clinically insignificant. We present an unusual case of infective endocarditis affecting only the Chiari network in a patient who presented with septic emboli to the lungs and brain. Case summary. A 61-year-old man was admitted with a 2-month history of hemoptysis, pleuritic chest pain, and right upper extremity numbness and weakness. He was found to have multifocal bilateral pulmonary opacities and an abscess collection in the brain. Blood cultures grew Streptococcus intermedius and transthoracic echocardiogram (TTE) was normal. Subsequent transesophageal echocardiogram (TEE) revealed an 8.3 × 4.6 mm vegetation arising from the Chiari network, close to the right atrial appendage, without involvement of the tricuspid valve or any of the other valves. There were no atrial or ventricular septal defects. He was treated with appropriate antibiotics with improvement of symptoms. Repeat imaging showed improvement of the lung opacities, but not the brain abscess, warranting transfer to another hospital for neurosurgical intervention. Conclusion. The diagnosis and management of isolated Chiari network endocarditis require a high index of clinical suspicion. A multidisciplinary approach incorporating both medical and surgical approaches where necessary is essential for optimal outcome.